PENGARUH TOTAL ASSET TURNOVER, RETURN ON ASSETS, DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2022–2024 - Yulia Variska Putri; Ida Subaida; Ardhya Yudistira Adi Nanggala (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Property and real estate companies play a crucial role in the economy, particularly in infrastructure development and housing provision. This study aims to examine the effect of Total asset turnover, Return on assets, and Current ratio on Company value, using Stock price as an intervening variable. This study focuses on property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 periods. The method used was quantitative with a descriptive approach, and purposive sampling was used to determine the sample. The data used in this study were secondary data obtained from the official IDX website, in the form of financial statements and annual reports during the study period. The data analysis in this study was conducted using the Structural Equation Modeling (SEM) method with the assistance of Smart PLS 3.0 software. The results show that the Total asset turnover has a negative but insignificant effect on Stock price and Company value. The Return on assets has a significant positive effect on Stock price and Company value. The Current ratio has a positive but insignificant effect on Stock price and Company value. The Stock price has a positive but insignificant effect on Company value. Indirectly, the Total asset turnover has a negative but insignificant effect on Company value through Stock price, while the Return on assets and Current ratio has a positive but insignificant effect through Stock price.